PERAN SUPERVISI DALAM TRANSFORMASI KURIKULUM: ANTARA TEORI DAN PRAKTIK - Robithulhaq, Muhammad; Bhekti Kurnianto, Denny; Bisyri, Kholil (As-Sulthan Journal of Education, 2024)
This study examines the role of supervision in curriculum transformation, focusing on the relationship between theory and practice in the field. Curriculum transformation is a crucial step in educational development to respond to the demands of the times. Educational supervision plays an important role in ensuring the successful implementation of a new curriculum. However, the application of supervision theory in the field often faces various challenges, such as limited resources, lack of training for supervisors, and resistance from educators. This study analyzes how supervision theory is translated into practice and identifies obstacles faced in the curriculum transformation process. The findings show that although supervision theory can be a guide, external and internal factors often affect its effectiveness. Therefore, alignment between supervision theory and practice is essential so that curriculum transformation can be achieved optimally. This study is expected to provide insight for educators and policy makers in improving the quality of supervision in supporting future curriculum changes.